DSTATCOM Application for Mitigation of Voltage Sag Caused by Dynamic Loads in Autonomous Systems - Ambarnath Banerji; Dr. Sujit K. Biswas; Bhim Singh (Institute of Advanced Engineering and Science, 2012)
This paper presents the application of distribution static compensator (DSTATCOM) for mitigating the frequently occurring problems of voltage dips in autonomous systems. Consumer loads are experiencing proliferation of induction motors. The starting of induction motors draws large current causing voltage sag (dip). Autonomous Power system is comparatively less stiff than the grid connected system. Large starting current, causing objectionable voltage drop, is critical for an autonomous system. DSTATCOM can be effectively used to redeem this power quality problem. An asynchronous generator with a motor load having a DSTATCOM connected in shunt is simulated on a MATLAB platform using Simulink and Power System Block set. The simulation establishes the capability of DSTATCOM to mitigate the voltage dip problem for an autonomous system.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.320